Simulation and Modeling of Moisture Distribution in Drip Irrigated Onion - Patel, Neelam; Rajput, T.B.S (Journal of Agricultural Engineering, 2009)
The design of drip irrigation system requires the knowledge of water distribution in the soil, which may be described and predicted by solving the flow through porous media equations. The software HYDRUS-2D simulates the three dimensional axi-symmetric water flow; solute transport, root water and nutrient uptake based on finite-element numerical solutions of the flow equations. In a field study, conducted for 3 years (1999-2002), HYDRUS-2D was used for simulation of moisture distribution pattern in the root zone of onion crop grown in sandy loam soil. The performance of HYDRUS -2D was evaluated by comparing its simulated value with the observed soil moisture patterns through certain indicators such as average absolute error (AAE), average relative error (ARE) and root mean square error (RMSE). Range of AAE (-5.65 to -2.86), ARE (0.112 to 0.147) and RMSE (3.58 to 6.10) indicate good match between simulated and observed soil moisture patterns, and hence, HYDRUS-2D is recommended for use as a tool for simulation ofsoil moisture distribution in onion fields.